Functional limitation as a mediator of the relationship between multimorbidity on health-related quality of life in Australia: evidence from a national panel mediation analysis - Lee, John Tayu; Ishida, Marie; Haregu, Tilahun; Pati, Sanghamitra; Zhao, Yang; Palladino, Raffaele; Anindya, Kanya; Atun, Rifat; Oldenburg, Brian; Marthias, Tiara (Frontiers in Medicine, 2023)
Objective The inverse relationships between chronic disease multimorbidity and health-related quality of life (HRQoL) has been well documented in the literature. However, the mechanism underlying this relationship is unknown. This is the first study to look into the potential role of functional limitation as a mediator in the relationship between multimorbidity and HRQoL. Method This study utilized three recent waves of nationally representive longitudinal Household, Income and Labour Dynamics in Australia (HILDA) survey from 2009-2017 (n=6,814). A panel mediation analysis was performed to assess the role of functional limitation as a mediator in the relationship between multimorbidity and HRQoL. The natural direct effect (NDE), indirect effect (NIE), marginal total effect (MTE), and percentage mediated were used to calculate the levels of the mediation effect. Result This study found that functional limitation as a significant mediator in the relationship between multimorbidity and HRQoL. In the logistic regression analysis, the negative impact of multimorbidity on HRQoL was reduced after functional limitation was included in the regression model. In the panel mediation analysis, our results suggested that functional limitation mediated approximately 27.2% (p<0.05) of the link between multimorbidity and the composite SF-36 score for HRQoL. Functional limitation also mediated the relationship between number of chronic conditions and HRQoL for each of the eight SF-36 dimensions, with a proportion mediated ranging from 18.4 to 28.8% (p<0.05). Conclusion Functional status has a significant impact on HRQoL in multimorbid patients. Treatment should concentrate on interventions that improve patients' functioning and mitigate the negative effects of multimorbidity.